Zasady rekrutacji i socjologiczna charakterystyka kobiet służących w OLK i WSK AK - Marcinkiewicz-Kaczmarczyk, Anna (Dzieje Najnowsze, 2015)
Principles of the Recruitment of Women Serving in OLK and WSK AK and Their Sociological Characteristic Polish women served as soldiers during both world wars. The Women’s Voluntary League (OLK) defended the frontiers of the Second Republic, and the Military Women’s Service (WSK) was established at the time of the Nazi occupation and functioned first within the Union of Armed Struggle (ZWZ) and then in the Home Army (AK). It should be emphasised that the attitude towards women’s military service in 1918–1922 differed from the one prevalent during the Second World War. The phenomenon in question was affected by social transformations and changing manners and morals as well as by the progress of military training during the inter–war period, the political– military situation in the years 1939–1945, and the fact that ZWZ–AK was not a regular army. This was the reason why the socio–legal situation of female members of the Legions and those of WSK ZWZ–AK was essentially different. The recruitment requirements in both formations varied considerably, since in the latter case no morality certificates or husbands’ consents were required. Moreover, women serving in WSK ZWZ–AK were not only much better educated than the female Legionaries but also in many instances completed military and professional training. Consequently, they met qualification demands for highest military ranks, which the Legionaries were never offered. The principles of women’s recruitment and the opportunities for promotion were much wider than in OLK, thus testifying that, i.a. the position of the woman in the army structures in the 1918–1945 period was considerably stronger.